Barriers to the Maintenance of COVID 19 Cross Infection Control Protocols among Medical and Dental Practitioners - Hira Butt, Hira Sheikh, Syed Ghyour Ali Mohsin, Nauman Rauf Khan, Tajwar Jafar, Taimur Hassan Shah, Maria Jabbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the barriers to the maintenance of COVID 19 cross infection control protocols among medical and dental practitioners Methodology: A cross sectional study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore from July 2021 to July 2022 on medical and dental practitioners. The sampling technique employed was convenient sampling. Medical and dental practitioners irrespective of their age, gender and specialty of practice were included in the study. Data was collected using a pre-validated questionnaire with a Cronbach alpha value of 0.7. Results: There was s statistically significant difference in the scores of barriers to maintenance of COVID 19 cross infection control protocols of overcrowding in the hospital (p= ≤0.001), limitation of infection control material (p=≤0.001), insufficient training in infection control (p=0.05), lack of handwashing (p=0.022), not wearing a mask while examining the patient (p=≤0.001) and lack of knowledge about mode of transmission of COVID 19 (P=0.036) Conclusion: The barriers faced to maintenance of cross infection control protocols pertaining to the hospital administration were reported to be higher for medical practitioners in comparison to the dental practitioners. The barriers faced to maintenance of cross infection control protocols pertaining to the attitude and practices of health care workers were also higher for medical practitioners in comparison to the dental practitioners. Keywords: Cross infection control, COVID 19 pandemic, medical practitioners, dental practitioners